2018
DOI: 10.1080/19490976.2018.1441664
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal androgen exposure causes hypertension and gut microbiota dysbiosis

Abstract: Background: Conditions of excess androgen in women, such as polycystic ovary syndrome (PCOS), often exhibit intergenerational transmission. One way in which the risk for PCOS may be increased in daughters of affected women is through exposure to elevated androgens in utero. Hyperandrogenemic conditions have serious health consequences, including increased risk for hypertension and cardiovascular disease. Recently, gut dysbiosis has been found to induce hypertension in rats, such that blood pressure can be norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 144 publications
(118 reference statements)
4
93
1
1
Order By: Relevance
“…that androgen-related gut microbiota changes are involved in PCOS pathophysiology. Fetal or neonatal androgen excess is also associated with dysbiosis in a model of PCOS, 47,48 supporting the idea that fetal and neonatal development affects longterm gut microbiota composition.…”
Section: Effect Of Androgens On Gut Microbiota In Femalesmentioning
confidence: 66%
“…that androgen-related gut microbiota changes are involved in PCOS pathophysiology. Fetal or neonatal androgen excess is also associated with dysbiosis in a model of PCOS, 47,48 supporting the idea that fetal and neonatal development affects longterm gut microbiota composition.…”
Section: Effect Of Androgens On Gut Microbiota In Femalesmentioning
confidence: 66%
“…Gut DHEAS may come from the excessive serum DHEAS and partly may be converted by the gut microbiota. Disordered gut microbiota and metabolites may act on multiple organs throughout the body by damaging the intestinal mucosal barrier, affecting the serum sex hormone levels, glycogen biosynthesis and metabolism, and causing systemic chronic inflammation (45,46). DHEAS in the intestinal and peripheral circulation of obese patients with PCOS may be freely exchanged, whereas too much androgens can affect the diversity and richness of gut microbiota (47).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated that the regulation of sex hormones–microbiota–inflammation axis could ameliorate polycystic ovary syndrome (PCOS), including Faecalibacterium, Parabacteroides, Bifidobacterium , and so on (Wang et al, 2020 ). Another study showed that prenatal androgen exposure causes hypertension and gut microbiota dysbiosis (Sherman et al, 2018 ). Moreover, a study found that small amounts of brain E2 and PROG could improve menopausal symptoms by decreasing serum FSH levels and maintaining the diversity of the gut microbiome in estrogen-deficient rats (Park et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%